The role of adaptation in protecting the economic balance of the contract "Comparative Legal Study" (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The topic " qualification of contract according to changes of performance circumstances" deals with the more importance of contract details. Because this treats the problems may be arise as results of break one or more parties as reaction the changes may obtain which breaks the balance of economical effects. However, the parties of contract to avoid these results, they lay down contractual terms resolve this problem, this way made the contract responds to performance equipment's  .